Advanced electrophysiological diagnostics of hepatic and portosystemic encephalopathy - Kuba, M; Kremlácek, J; Hůlek, P; Kubová, Z; Vít, F (Acta medica (Hradec Kralove), 1996)
In 28 patients with liver cirrhosis, pre- and post-TIPS (transjugular intrahepatic porta-caval shunt), pattern-reversal visual evoked potentials (PREPs) and motion-onset visual evoked potentials (M-VEPs) examinations, EEG spectral analysis and Number Connection Test were performed. The M-VEPs (representing an activity of the magnocellular system of the visual pathway and reactions of the mediotemporal associate visual area) displayed the highest sensitivity (latencies delay) for detection of subclinical hepatic encephalopathy. The PREPs (originating in the primary visual cortex -area striata) were not significantly changed in comparison with a group of age matched controls. The EEG frequency spectrum exhibited significant slowing of the dominant frequency which was more pronounced in the post-TIPS examination. Combined analysis of the M-VEPs latency and EEG dominant frequency seem to be a recommendable method for early detection and objective classification of subclinical hepatic or portosystemic encephalopathy.
Keywords: Evoked Potentials, Visual; Electroencephalography; zrakové evokované potenciály; Hepatic Encephalopathy; Adolescent; elektroencefalografie; Adult; Aged; dospělí; senioři; jaterní encefalopatie; mladiství; lidé; Humans; Sensitivity and Specificity; senzitivita a specificita; Portasystemic Shunt, Transjugular Intrahepatic; lidé středního věku; transjugulární intrahepatální portosystémový zkrat; Middle Aged